Exploring the interplay between social media addiction, mindful eating, intuitive eating, orthorexia nervosa, and mental health in young adults - Bayram, Hatice Merve; Barcın-Guzeldere, Hatice Kübra; Ede-Cintesun, Elif; Celik, Zehra Margot (The North African Journal of Food and Nutrition Research, 2024)
Background: Considering the reported negative effects of social media on mental health and the popularity of healthy eating movements on these platforms, a potential relationship between orthorexia nervosa (ON), intuitive eating, mindful eating, and social media addiction warrants investigation.Aims: This study aimed to explore the complex relationship between social media addiction, mindful eating, intuitive eating, ON, depression, anxiety, and stress in young adults.Subjects and Methods: A cross-sectional study was conducted on 303 students, in Istanbul, Türkiye, between December 2023 and May 2024. Participants completed an online questionnaire assessing demographic characteristics, Orthorexia Nervosa Questionnaire (ORTO-11), Intuitive Eating Scale – 2nd edition (IES-2), Mindful Eating Questionnaire (MEQ), Depression, Anxiety, Stress Scale-Short Form (DASS-21), and Social Media Addiction Scale (SMAS). Body weight and height information were self-reported. Data were analyzed using SPSS 24.0.Results: Of the participants, 67.7% were at risk of ON. According to ON classification, IES-2 and SMAS scores of participants with the risk of ON were higher and statistically significantly different compared to the participants with no risk of ON (p < 0.001, and p = 0.047, respectively).  The ORTO-11 showed a positive moderate correlation with IES-2 scores (r = 0.401, p < 0.01), however, it showed a negative weak correlation with MEQ (r = -0.362, p < 0.01). Additionally, there was a negative weak correlation with ORTO-11 and SMAS (r = -0.104, p < 0.05). Logistic regression analysis revealed that all predictors were associated with the risk of ON. These variables predicted 13% of the variance.Conclusion: The results suggest that modern social media may contribute to orthorexic symptoms, mindful and intuitive eating behaviors, and mental health outcomes. Keywords: intuitive eating, mindful eating, orthorexia nervosa, social media addiction.